P. 1
1a 2009 Logarithm

1a 2009 Logarithm

4.0

|Views: 164|Likes:
Published by fabremil7472

More info:

Published by: fabremil7472 on Dec 23, 2008
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as DOC, PDF, TXT or read online from Scribd
See more
See less

06/14/2009

pdf

text

original

Logarithms In this chapter you must be able to (i) understand the relationship between logarithms and indices, and use

the laws of logarithms (excluding change of base) (ii) understand the definition and properties of ex and ln x, including the relationship as inverse functions and their graphs Relationship between log and indices Let x = a p ⇔ loga x = p ; y = a q ⇔ loga y = q xy = a p . a q = a p + q ; log a xy = log a x + log a y
x ap = = a p−q y aq

;

log a

x = log a x − log a y y
n

x n = (ap )n = ap n = log a x log a a = 1 ; log a 1 = 0 i) Express log
1

= n log a x

x3

y ii) Express 3 log 8 − log 2 5 as a single logarithm. iii) Solve the equation log 6 x + log 6 ( x + 5) = 2 . Graphs of ex and ln x

in terms of log x and log y.

(3logx − 12 logy)

(log5)
(x = 4; x = −9(not acceptable))

1

y y

y=ex

y = ln x

x

Note these two: (1) e ln x = x 1 Solve for x i) ex - 2 - 3e-x = 0 ii) e 3t + 2et = 3e2t

(2) ln e x = x ( x = ln 3) (t = 0, ln 2)

2

iii) - 2 ln x = b iv) 3 ln x – ½ ln x = 5 v) ln x = 2 ( ln 3 - ln 5 ) vi) ak – ekx = 0 vii)x ln x = e viii) 2 + 5 e − 4x = 3 ix) - ln x = x) ln x =
1 3 t 50

(x = e 2 ) (x = e2 )
( x = 9 25)

−b

( x = ln a ) ( x = e, e −1 )

+c ( x = 4) = 1 + ln a

(ln 16 + 2 ln 2) 2x)

xi) ax = e 2x +1 xii) 2 (ln 1 ( x = ± 2 ae ) xiii)32x = 42 – x xiv)ex - 2e— x = 1

2 Solve the following equations giving x correct to 3 significant figures. ( x = 0.642) a) 7x . 8 2x - 1 = 6.3 b) c) d) e) 32x – 3x +2 + 8 = 0 2x = 3 3x+1 = 18 2x . 32x = 5
( x = 0 ; 1.893)

( 0.5568)

3 Solve for x a) ex ( 1 - 2x ) = 0 ( x = 12) b) e-x ( 1 + x ) = 0
{e −x = 0 (not possible); x = −1} ( dont cancel; x = 1)

c) d)

xex = ex ex - e-x = 6

(1.818)
ln 3 ln 2

4 By using a suitable substitution, solve the following equations: a) 2 2x - 5 . 2x + 6 = 0 b) 32x + 1 + 32 = 3x + 3 + 3x
5
(x = = 1.5849; x = 1)

( x = −1; x = 2)

If y = ln ( 1 + 6x + 8x2 ) - ln ( 1 + 5x + 4x2 ) + ln ( 1+ x )- ln (1 + 2x ), prove that y is independent of x.

6 Solve for x and y : a) x - y = 1 ; 2x . 3y = 432

3

b) log x + log y = log 10 ; log x - log y = log 2.5 c) 2x . 4- y = 2 ; 3- x . 92y = 3 d) log x + log y = 1 ; log x - log y = log 2.5 e) x1/2 + y 2/3 = 6 ; x
- 1/2

( x = 3, y = 1) ( x = 5, y = 2)
3

+y

- 2/3

f) log 2 (xy 2) = 4 ; log 2 x . log 2 y = 2 7) log 4 2 . log 4 ( 1 2 x ) = log 4 x

( x = 16, y = 2 2 ; x = 4, y = 8) ( x = 4, y = 2)

8) Express ln (2√ e) - 1/3 ln (8/e) - ln (e/3) in the form c + ln d. (− 1 6 + ln 3)

4

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->